Quantitative analysis of teacher evaluation performance at University of Costa Rica - Ruiz Barrantes, Esteban Alberto (2021)
This article analyzes evaluations of teaching performance carried out in the second school period of 2018, by the Center of Academic Evaluation (CEA) of University of Costa Rica (UCR) in order to provide information on the implementation of strategies for the continuous improvement of teaching performance using a quantitative approach with a descriptive scope. A total of 57 148 evaluations were analyzed, which correspond to 5 082 groups and 1 772 university courses. A cluster analysis and several correspondence analyzes were performed. Among the main findings, it is denoted that a majority of teachers are well evaluated, since 88.1% have an average evaluation greater than or equal to 8 (scale from 0 to 10). A higher proportion of teachers was found classified according to the analysis as very good, mainly composed of women and courses with groups from 1 to 10 students. It was determined that there is a higher proportion of teachers with advanced ages or large groups that favor a negative attitude towards the subject, as well as advanced students in career or with working conditions with this attitude. The arts, letters and education courses promote a better interest towards the subject compared to the courses in basic sciences, engineering, economic sciences and general studies, where little interest and loss of interest are aspects that are reflected in a greater proportion. As a new research horizon at UCR, it is suggested to study the relationship between teacher evaluation grade and the effect of the attitude developed towards the subject on variables such as students’ grades and hours they dedicate to the course.